How do you verify ##(1-cos^2x)(1+cos^2x)=2sin^2x-sin^4x##?

Prove ( 1 – cos ^2 x) (1 + cos^2 x) = 2sin^2 x – sin^4 x

Replace ##( 1 – cos^2 x)## by ##sin^2 x## and ##cos^2 x## by ##1 -sin^2 x##, we get:
##(1 – cos ^2 x) (1 + cos^2 x)## =
##sin^2 x ( 1 + 1 – sin^2 x) ##=
##sin^2 x (2 – sin^2 x) = 2sin ^2 x – sin^4 x##

Posted in Uncategorized

Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes:

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>